Combined stimuli of elasticity and microgrooves form aligned myotubes that characterize slow twitch muscles - Hiroki Hamaguchi; Tomoko G. Oyama; Kotaro Oyama; Yasuko Manabe; Nobuharu L. Fujii; Mitsumasa Taguchi (Scientific Reports)
Abstract Skeletal muscles are classified into slow-twitch muscles composed primarily of type I and IIa fibers with high oxidative metabolism, and fast-twitch muscles composed of type IIx and IIb fibers with high glycolytic metabolism. Fiber-type shifts occur during development and aging; however, the stimuli that shift these types remain unclear. We analyzed the role of mechanical stimuli in myotube formation and shift to the characteristics of each fiber type using crosslinked gelatin gels with tunable elastic moduli (10–230 kPa) and microgrooves (3–50 µm). C2C12 myotubes on 10 kPa gel increased the expression of marker genes for type I and IIa fibers (MYH7 and MYH2) and oxidative metabolism (GLUT4 and myoglobin) than those on stiffer gels. Upregulation of PGC-1α on soft gel induced a shift toward slow-twitch muscle genetic characteristics. Microgrooves (3–10 µm) enhanced myoblast differentiation and myotube orientation, without affecting the gene expressions characterizing fiber types. This study demonstrated an approach to create highly oriented slow-twitch muscle models by controlling the elasticity and microgrooves.